1981
DOI: 10.1007/bf01249132
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing monoamine metabolites and tryptophan in patients with alcohol dependence

Abstract: Cerebrospinal fluid 5-hydroxyindoleacetic acid (5-HIAA), homovanillic acid (HVA) and tryptophan (TRY) were measured in 36 female patients with alcohol dependence defined by strict operational criteria. Results were compared with a control group of 32 women hospitalized in a neurological unit for peripheral diseases. Several disorders presumably interfering with monoamine metabolism were excluded and diet, psychomotor activity, diurnal variation, nutritional state and similar nonspecific variables controlled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(32 citation statements)
references
References 30 publications
(25 reference statements)
1
30
1
Order By: Relevance
“…Compared to controls, alcoholics have low CSF levels of 5-hydroxyindoleacetic acid (5-HIAA), the major metabolite of 5-HT (Gorelick 1989;Roy et al 1990). Furthermore, an inverse relationship between CSF 5-HIAA levels and the time elapsed since alcohol was last consumed has been observed in alcoholics (Banki 1981). These findings suggest that drinking in alcoholics may serve to increase low 5-HT activity.…”
mentioning
confidence: 75%
“…Compared to controls, alcoholics have low CSF levels of 5-hydroxyindoleacetic acid (5-HIAA), the major metabolite of 5-HT (Gorelick 1989;Roy et al 1990). Furthermore, an inverse relationship between CSF 5-HIAA levels and the time elapsed since alcohol was last consumed has been observed in alcoholics (Banki 1981). These findings suggest that drinking in alcoholics may serve to increase low 5-HT activity.…”
mentioning
confidence: 75%
“…Serotonin dysfunction has been correlated with impulsive and violent criminal behaviors (Brown et al , 1982Lidberg et al 1985;Limson et al, 1991;Virkkunen and Närvänen 1987;Virkkunen et al 1994aVirkkunen et al , 1994b, alcohol abuse and dependence (Badawy et al 1995;Ballenger et al 1979;Banki 1981;Borg et al 1985;Moss 1987;Roy and Linnoila 1989), Gilles de la Tourette's syndrome (Butler et al 1979;Cohen et al 1978Cohen et al , 1979, bulimia (Jimerson et al 1990(Jimerson et al , 1992, and suicide attempts (Asberg et al 1976(Asberg et al , 1986Banki and Arato 1983;López-Ibor et al 1985), as well as with children institutionalized for aggressive behavior (Kruesi 1989;Kruesi et al 1990Kruesi et al , 1992.…”
Section: Plasma L -Tryptophan (Trp) Reductions Have Been Related To Amentioning
confidence: 99%
“…For example, Balldin and colleagues (Balldin et al 1994) found that human subjects with modestly elevated rates of alcohol consumption (below 107 g per day, mean consumption 85 g per day) were particularly likely to reduce their alcohol consumption after SSRI treatment as compared with subjects with very high consumption rates (above 107 g, mean consumption 138 g per day). On the other hand, studies show that primates with the lowest CNS serotonin functioning tend to be the highest alcohol consumers (Higley et al 1991, and alcoholics and sons of alcoholics also show low CNS serotonin functioning Banki 1981;Borg et al 1985). It is therefore not unreasonable to predict that the subjects with the highest consumption patterns would benefit most from SSRI treatment.…”
mentioning
confidence: 99%